Apoptosis Induction in Colon Cancer Cell Lines and Alteration of Aberrant Crypt Foci in Rat Colon by Purple Rice (Oryza sativa L. var. glutinosa) Extracts - Wongjaikam S. (Routledge, 2014)
Crude ethanol extracts (CEE) of purple rice was fractionated to obtain hexane soluble (HSF) and ethyl acetate soluble fractions (EASF). Total antioxidant capacity was higher in CEE than the HSF and EASF. However, HSF exhibited strong antiproliferation and apoptosis induction against colon cancer cell lines, both p53 wild-type (RKO) and mutant (SW620) strains. Then, the CEE was used to determine the effects on the progression of aberrant crypt foci (ACF), a preneoplastic lesion seen in colon carcinogenesis in rats. Male Wistar rats were subcutaneously injected of 40 mg/kg body weight dimethylhydrazin (DMH) once weekly for 2 wk. After 2 wk, rats were orally administered ethanol extract at 100 and 1000 mg/kg body weight, for 4 wk. Rats fed with only the high dose of CEE had significantly decreased numbers of ACF per rat (45.56%) and crypt multiplicity (AC/focus) (16.67%) compared to rats that received DMH alone. The result also demonstrated that CEE induced apoptosis in colonic epithelium cells of rat received colon carcinogen as detected the increasing of caspase-3 activity. This finding could be concluded that purple rice extracts inhibited aberrant colonic epithelial cell progression via apoptosis induction. © 2014 Copyright Taylor & Francis Group, LLC.